L'éducation esthétique selon Schiller Une contribution à l'archéologie du libéralisme - Raulet, Gérard (La croisée des chemins, 2023)
According to a widely held view, Schiller is Kant's heir and successor, and the Letters on the Aesthetic Education of Man are a testimony to his creative adherence to Kantianism through the conception of a new relationship between theory and practice. The book goes against this commonly held idea. It attempts to renew the interpretation of Schiller's text and, in particular, it shows the influence of pre-critical popular philosophy, especially its anthropological component. The conjunction of this register with a singular reading of Kantian aesthetics appears as characteristic of a form of thought that can be described as conservative reformism and which should be seen as the matrix of the political liberalism that emerged at the beginning of the 19th century. The book's thorough philological interpretation will appeal both to specialists of Kantian and post-Kantian thought and to students seeking an introduction to Schiller's Letters.